Instantaneous and historical temperature effects on α -pinene emissions in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Llusia, Joan; Niinemets, Ülo; Noe, Steffen M.; Penuelas, Josep (Journal of Environmental Biology, 2011)
We compared the role of instantaneous temperature and temperature history in the determination of α-pinene emissions in Mediterranean conifer Pinus halepensis that stores monoterpenes in resin ducts, and in Mediterranean broad-leaved evergreen Quercus ilex that lacks such specialized storage structures. In both species, α-pinene emission rates (E) exhibited a significant exponential correlation with leaf temperature and the rates of photosynthetic electron transport (JCO 2 +O 2 ) started to decrease after an optimum at approximately 35 o C. However, there was a higher dependence of E on mean temperature of previous days than on mean temperature of current day for P. halepensis but not for Q. ilex. JCO 2 +O 2 showed a maximum relationship to mean temperature of previous 3 and 5 days for P. halepensis and Q. ilex respectively. We conclude that although the best correlation of emission rates were found for instantaneous foliar temperatures, the effect of accumulated previous temperature conditions should also be considered in models of monoterpene emission, especially for terpene storing species.
Keywords: acclimation; emission model; Pinus halepensis; previous climate effects; Quercus ilex

The Mediterranean evergreen Quercus ilex and the semi-deciduous Cistus albidus differ in their leaf gas exchange regulation and acclimation to repeated drought and re-watering cycles - Galle, Alexander; Florez-Sarasa, Igor; Aououad, Hanan El; Flexas, Jaume (Journal of Experimental Botany, 2011)
Plants may exhibit some degree of acclimation after experiencing drought, but physiological adjustments to consecutive cycles of drought and re-watering (recovery) have scarcely been studied. The Mediterranean evergreen holm oak (Q. ilex) and the semi-deciduous rockrose (C. albidus) showed some degree of acclimation after the first of three drought cycles (S1, S2, and S3). For instance, during S2 and S3 both species retained higher relative leaf water contents than during S1, despite reaching similar leaf water potentials. However, both species showed remarkable differences in their photosynthetic acclimation to repeated drought cycles. Both species decreased photosynthesis to a similar extent during the three cycles (20–40% of control values). However, after S1 and S2, photosynthesis recovered only to 80% of control values in holm oak, due to persistently low stomatal (gs) and mesophyll (gm) conductances to CO2. Moreover, leaf intrinsic water use efficiency (WUE) was kept almost constant in this species during the entire experiment. By contrast, photosynthesis of rockrose recovered almost completely after each drought cycle (90–100% of control values), while the WUE was largely and permanently increased (by 50–150%, depending on the day) after S1. This was due to a regulation which consisted in keeping gs low (recovering to 50–60% of control values after re-watering) while maintaining a high gm (even exceeding control values during re-watering). While the mechanisms to achieve such particular regulation of water and CO2 diffusion in leaves are unknown, it clearly represents a unique acclimation feature of this species after a drought cycle, which allows it a much better performance during successive drought events. Thus, differences in the photosynthetic acclimation to repeated drought cycles can have important consequences on the relative fitness of different Mediterranean species or growth forms within the frame of climate change scenarios.
10.1093/jxb/err23310.1093/jxb/err233
Keywords: acclimation; drought–recovery cycles; mesophyll and stomatal conductance; osmotic adjustment; photosynthetic limitation analysis; water use efﬁciency

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature